Ankle Brachial Index (ABI) Score in Patient with Type 2 Diabetes Mellitus - Komang Agus Jerry Widyanata; I Ketut Widya; Ni Luh Putu Suardini Yudhawati (Babali Health, 2022)
Introduction: Unstable blood glucose levels in patient with Type 2 Diabetes Mellitus (DM) can cause various complications, one of which is peripheral neuropathy. Peripheral neuropathy is caused by atherosclerosis. The incidence of atherosclerosis can be seen by assessing the Ankle Brachial Index (ABI). This study aims to describe the ABI score in type 2 DM patients. Methods: The design of this study is a descriptive observational located at the Wirasatya Army Hospital, Singaraja in April 2022. The subjects were 81 patients with type 2 DM. The sampling technique used is purposive sampling. Measurement of the ABI score is carried out using an Oscillometric Sphygmomanometer. Descriptive analysis is used in this study and presented by frequency distribution. Results: This study found that 33.3% of subjects aged 44-55 years, 63.0% of subjects of male, 77.8% of subjects suffering from type 2 DM between 1 to 5 years, 32.1% working as entrepreneurs, and 78.2% having ABI scores between 1.0-1.4 so that they are included in the normal category. Conclusion: Patients with type 2 DM in the age group of 44-55 years, male, suffering from type 2 DM between 1 to 5 years, working as self-employed and more have normal ABI scores.